Assessment of Protein Turnover in Health and Disease. (1st March 2017) - Wernerman, Jan; Morris, Claudia R.; Paddon‐Jones, Douglas; Sarav, Menaka
Abstract : To identify protein requirements, it is necessary to be familiar with basic physiology, practical methods, and dose response of protein delivery. This review evaluates available methodology, with emphasis on the limitations of existing techniques most often related to the underlying assumption. Historically, nitrogen balance has been the dominating technique. It is still the gold standard, although there are considerable problems related to the underlying assumptions to have reliable readings. When minimal requirements needed to be defined, the indicator amino acid oxidation technique came into practice. In situations of longer term steady states, it serves a purpose. In situations of disease or in aging, it has proven to be more problematic. More recently, whole‐body protein turnover measurements have shown to be useful in situations where the underlying assumptions for the other techniques are not possible to meet.